Issues of measuring and interpreting wind direction. Issue 1 (2nd January 2022) - Knight, Jasper; Fitchett, Jennifer M.
ABSTRACT: This study highlights a significant methodological and practical issue involving the use of a magnetic compass in aeolian studies in the field. Geomagnetic declination can significantly affect field measurements of wind direction from anemometers as well as measurement of the orientation of geomorphic features such as sand dunes, depending on geographic location. It is therefore surprising how often methodological descriptions of published aeolian studies, including those in southern Africa, neglect to describe any declination corrections applied to field measurements or instrumental records. This results in uncertainty in the validity of data reported in such studies, particularly where actual wind directions may be very different (>20° in some cases) from measured values. Drawing from examples in the literature from southern Africa and other key locations globally, this study discusses the need for greater clarity in the declination corrections applied when wind direction is being measured and reported, especially where wind datasets from different sources are being used or integrated, or when published studies are being compared.